2009
DOI: 10.1002/j.2048-7940.2009.tb00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Participation of Middle-Aged and Older Latin-American Women in Physical Activity: A Stroke-Prevention Behavior

Abstract: Despite the known benefits of regular physical activity for preventing stroke and cardiovascular disease, middle-aged and older Latin-American women continue to be physically inactive and demonstrate a high incidence of obesity. Ethnographic methodology was used to explore factors that influenced this health behavior in 25 Latin-American women. Perceptions of health, the health activities in which they engaged, and the factors that influenced their participation in physical activity comprised the three categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 17 publications
4
38
1
2
Order By: Relevance
“…Another study also revealed physical illness as a barrier to physical activity [25]. It appears that for fall prevention strategies to be effective, exercise educational programs should not be undertaken in isolation, but in partnership with other interventions and integrated into generic health.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also revealed physical illness as a barrier to physical activity [25]. It appears that for fall prevention strategies to be effective, exercise educational programs should not be undertaken in isolation, but in partnership with other interventions and integrated into generic health.…”
Section: Discussionmentioning
confidence: 99%
“…Both internal and external barriers have been identified as real challenges to physical activity participation for persons with conditions managed by physical therapists, including osteoarthritis, 29 chronic pain, 1,21 low back pain, 16,19 and stroke. 36,45 There is limited research on interventions to change internal barriers to physical activity, and fostering long-term change in physical activity participation has had only partial success. For example, education on the benefits of physical activity, counseling to support change, referral to exercise groups, and selfefficacy training have all been found to improve short-term physical activity participation but not to support long-term change.…”
Section: T T Resultsmentioning
confidence: 99%
“…A large modification index also suggested inserting a direct path from barriers to outcome expectations. This path was added based on research that supports barriers being inversely related to benefits of PA (Vaughn, 2009). Thus it was expected that individuals who perceive more barriers to PA would have less positive outcome expectations.…”
Section: Path Analysismentioning
confidence: 99%